Unsupported walking with only half of the brain due to severe porencephaly - Josef Finsterer (Journal of Family Medicine and Primary Care)
A patient with a history of Asian flu, mumps meningo-encephalitis, and skull-base fracture and severe porencephaly who was able to walk without assistance, has not been reported. The patient is a 65 year-old male with a history of Asian flu at 6 months of age, Mumps meningoencephalitis at 6 years of age, structural epilepsy since 15 years of age, traumatic brain injury with skull-base fracture at 51 years of age, arterial hypertension, diabetes, hyperlipidemia, previous alcoholism, and polyneuropathy. He presented with only mild right-sided spastic hemiparesis, dysarthria, decreased tendon reflexes in the lower limbs, spastic-ataxic gait, but he was able to walk unassisted. Cerebral MRI showed massive porencephaly with left lateral and third ventricular hydrocephalus. It was concluded, that patients with severe hemihydrocephalus since childhood may still be able to walk without support.